Perlindungan Perempuan Korban Kekerasan Dalam Rumah Tangga Menurut Sistem Hukum Indonesia Dan Sistem Hukum Islam - Sukamarriko Andrikasmi; Emilda Firdaus (Faculty of Law Universitas Lancang Kuning, 2020)
Women are creatures of God Almighty, just as men have natural rights that are inherent and must be protected. In the Islamic legal system, women get a glorious position and many letters in the Qur'an tell about women. Yet today's tendency, many violations of women's human rights, especially occur in the domestic so-called domestic violence.This study raises the problem of how the protection of women victims of domestic violence according to the Indonesian legal system and Islamic legal system and how the ideal future form of protection of women victims of domestic violence. This type of research is normative juridical, using secondary data types. The results showed that the protection of women victims of domestic violence in the legal system of Indonesia already has a legal umbrella that is Law No. 23 of 2004 on the Elimination of Domestic Violence, but there are still weaknesses, while the protection of women victims of domestic violence in the Islamic legal system refers to Al Quran and Hadith especially in the Surah An Nisa but need to be interpreted contextually not just textual. The ideal form of protection of women victims of domestic violence in the future that is the articles in the Act abolition of domestic violence should apply the principles of marriage in Islamic law, so as to create peaceful, peaceful and eternal home forever